Online continuing education for midwives in China: current trends, barriers, and future directions - Yao Zhang; Qinqi Deng; Xiaolong Zheng; Xinfen Xu; Fang Wang (BMC Medical Education)
Abstract Aim This study investigated the state of online continuing education for midwives in China via a web-based questionnaire, identified current trends, explored potential barriers, predicted future research directions, and provided insights into improving the effectiveness and quality. Background The COVID-19 pandemic necessitated the shift from in-person to long-distance online education, significantly modifying continuing education for midwives. Online continuing education is crucial in improving midwifery skills and has been widely adopted in China. Design A cross-sectional design was used. Methods This study used a cross-sectional design with convenience sampling. Data were collected from midwives working in Level I to Level III hospitals across 31 provinces of mainland China through an online questionnaire platform called WenjuanXing from October 2021 to April 2022. Results A total of 12,122 midwives participated, of which 10,102 (83.34%) had previously attended online courses, primarily using DingTalk (52.79%), Tencent Meeting (48.75%), and WeChat (44.4%) for online learning. More than half of the participants had experienced blended learning (59.74%) rather than only online learning (31.54%). Most participants (10,541, 84.38%) had limited knowledge of online continuing education. Flexible scheduling (94.76%) was the top reason for participation, whereas clinical work pressure (85.9%) was the main barrier. 10,315 (85.09%) participants preferred more interactive online learning methods. Ordered logistic regression analysis revealed that geographic location, demographic factors, employment characteristics, and hospital attributes significantly influenced healthcare professionals' willingness to use online resources. Midwives in Central regions, unmarried, elderly, highly educated, non-formally employed, working in obstetrics wards, and lower-tier hospitals showed a higher inclination for online continuing education. Conclusion With rapid technological advancements, online continuing education offers a valuable way for clinical midwives to obtain up-to-date information and knowledge. However, it remains in the early stages and requires further development.